Childhood sleep disturbance and risk of psychotic experiences at 18: UK birth cohort. (July 2015) - Thompson, A.; Lereya, S. T.; Lewis, G.; Zammit, S.; Fisher, H. L.; Wolke, D.
Abstract : Background: Sleep disturbances are commonly reported in the psychosis prodrome, but rarely explored in relation to psychotic experiences. Aims: To investigate the relationship between specific parasomnias (nightmares, night terrors and sleepwalking) in childhood and later adolescent psychotic experiences. Method: The sample comprised 4720 individuals from a UK birth cohort. Mothers reported on children's experience of regular nightmares at several time points between 2 and 9 years. Experience of nightmares, night terrors and sleepwalking was assessed using a semi-structured interview at age 12. Psychotic experiences were assessed at ages 12 and 18 using a semi-structured clinical interview. Results: There was a significant association between the presence of nightmares at 12 and psychotic experiences at 18 when adjusted for possible confounders and psychotic experiences at 12 (OR = 1.62, 95% CI 1.19–2.20). The odds ratios were larger for those who reported persistent psychotic experiences. Conclusions: The presence of nightmares might be an early risk indicator for psychosis.